TO THE ISSUE OF THE ESSENCE OF CRIMINALISTIC RESEARCH OF CRIMINAL CASE FILES AND ITS LEGALISATION IN CRIMINAL PROCEEDINGS - MAKARENKO Ilona Anatolievna; EKSARKHOPULO Aleksey Alekseevich (Правовое государство: теория и практика)
The current Code of Criminal Procedure of the Russian Federation does not provide for such a procedural action as research of the criminal case files. It is mentioned mainly in commentaries, clarifications of higher courts or departmental regulations. The exception is part 1 of Article 58 of the Code of Criminal Procedure of the Russian Federation, where such research is named as one of the spheres of application of technical means by a specialist. The purpose of this publication is to define the essence of criminalistic research of criminal case files and its legalisation in criminal proceedings. Methods: analysis of normativelegal regulation, formal-legal, comparativelegal. Results: the article defines the components of criminalistic research of criminal case files, the grounds for studying these files, the range of circumstances to be clarified in the application of special knowledge; it also reveals the topical issues of legalisation of criminalistic research of criminal case files.